1995
DOI: 10.1016/0925-4773(95)00383-5
|View full text |Cite
|
Sign up to set email alerts
|

Murine Wnt-11 and Wnt-12 have temporally and spatially restricted expression patterns during embryonic development

Abstract: The Wnt gene family encodes a set of signalling molecules implicated in the development of a wide range of organisms. We have recently cloned partial cDNA sequences of murine Wnt-11 and Wnt-12. Here, we describe the spatio-temporal expression patterns of both genes during mouse embryogenesis. Wnt-11 expression is first detected within the truncus arteriosus from 8.25 dpc. By 9.5 dpc, Wnt-11 expression is detected in the somites at the medial junction of the dermatome and the myotome. Wnt-11 transcripts are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(84 citation statements)
references
References 36 publications
3
79
0
2
Order By: Relevance
“…Some Wnt genes can behave in an oncogenic fashion, as exempli®ed by Wnt1 (Christiansen et al, 1996). While no Wnt gene mutations have been associated with Wilms' tumour and Wnt4 has never been reported to behave in this fashion, Koester and Ridder (1999) demonstrated that 15% (6 out of 40) of WTs, harbour heterozygous missense/microdeletion mutations in the b-catenin proto-oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…Some Wnt genes can behave in an oncogenic fashion, as exempli®ed by Wnt1 (Christiansen et al, 1996). While no Wnt gene mutations have been associated with Wilms' tumour and Wnt4 has never been reported to behave in this fashion, Koester and Ridder (1999) demonstrated that 15% (6 out of 40) of WTs, harbour heterozygous missense/microdeletion mutations in the b-catenin proto-oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…In cells responding to canonical Wnt signaling, ␤-catenin is stabilized and enters the nucleus to activate the Tcf/Lef family transcription factors and regulate transcription of downstream genes. Although several Wnt genes as well as Tcf1 and Lef1 are known to be expressed in the developing facial primordia (Gavin et al, 1990;Oosterwegel et al, 1993;Parr et al, 1993;Christiansen et al, 1995;Wang and Shackleford, 1996), a direct role for Wnt signaling in facial morphogenesis was not known until recently. In search for genes conferring susceptibility to spontaneous CLP in the A strains of mice, Juriloff and colleagues genetically mapped an essential causal recessive mutation, clf1, to a small region of mouse chromosome 11 containing the closely linked Wnt3 and Wnt9b genes (Juriloff and Mah, 1995;Juriloff et al, 1996Juriloff et al, , 2001.…”
Section: The Wnt Pathwaymentioning
confidence: 99%
“…This once more raises the question of whether the placodes originate from a common structure, i.e., a mammary line. Guided by the knowledge that Lef1 (Van Genderen et al, 1994;Mailleux et al, 2002) and Wnt10b (Christiansen et al, 1995) are expressed in the mammary rudiments at E11.5-E12.5 and that the mammary rudiments are absent in E13.5 mouse embryos either lacking Lef1 expression (Van Genderen et al, 1994) or overexpressing the WNT inhibitor Dkk1 in the skin (Andl et al, 2002), we decided to examine the expression of Wnt genes in the mammary region of the mouse embryo by in situ hybridization. We show here that expression of Wnt10b precedes the appearance of mammary placodes.…”
Section: Introductionmentioning
confidence: 99%